1989
DOI: 10.1128/mcb.9.12.5602
|View full text |Cite
|
Sign up to set email alerts
|

The Saccharomyces cerevisiae SPT13/GAL11 gene has both positive and negative regulatory roles in transcription.

Abstract: To understand the function of SPT13, a gene encoding a trans-acting factor involved in regulation of Ty-mediated gene expression, we (13,17,50,60,66). Ty element insertion mutations often reduce adjacent-gene transcription, whereas solo 8 insertion mutations often alter adjacent-gene transcription qualitatively by providing an alternate and preferred site for transcription initiation (29,59,69). In both cases, the change in the pattern of transcription of the adjacent gene can lead to a mutant phenotype. Fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
88
0

Year Published

1991
1991
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 102 publications
(91 citation statements)
references
References 70 publications
3
88
0
Order By: Relevance
“…We suggest therefore that GALli protein functions as a basal transcription factor of some genes and that the GAL1l dependency is determined by the promoter context of the genes. This is consistent with the observations that the function of GALlI is pleiotropic (15,16,21,22). Since GALli protein did not bind a specific DNA sequence as judged by footprint analysis (H.S., unpublished results), it may regulate the basal transcription by protein-protein interactions with the basal or general transcription factors.…”
Section: Resultssupporting
confidence: 79%
See 1 more Smart Citation
“…We suggest therefore that GALli protein functions as a basal transcription factor of some genes and that the GAL1l dependency is determined by the promoter context of the genes. This is consistent with the observations that the function of GALlI is pleiotropic (15,16,21,22). Since GALli protein did not bind a specific DNA sequence as judged by footprint analysis (H.S., unpublished results), it may regulate the basal transcription by protein-protein interactions with the basal or general transcription factors.…”
Section: Resultssupporting
confidence: 79%
“…They further find that GALII is required for normal functioning of PPR1, an activator for the URA3 gene. Puzzlingly, GALI is also involved in the transcriptional repression of genes, since a loss-of-function mutation of GALII, called sptl3, restores the transcription of genes inactivated by insertion of the yeast transposon Ty (22).…”
Section: Al (21) Isolated a Mutantmentioning
confidence: 99%
“…The Gal11 subcomplex contains the Gal11, Pgd1, Sin4, Med2, and Rgr1 proteins, and mutations in the genes encoding these proteins can affect either transcriptional activation or repression, depending on the promoter . For example, a gal11 mutation results in reduced expression of SUC2, CTS1, and mating type genes, and increased expression of GAL1 and Ty1 genes (Fassler and Winston 1989;Vallier and Carlson 1991;Chen et al 1993;Sakurai and Fukasawa 1997). Gal11 functions as a strong activator when artificially recruited to DNA (Barberis et al 1995), and Gal11 interacts with TFIIE (Sakurai and Fukasawa 1997).…”
mentioning
confidence: 99%
“…For example, SPT13 (GAL11) is a negative regulator of Tyl transcriptional activity but a positive regulator of some mating-specific genes such as MFal (14). (The SPT13 and GALII genes were identified by different mutational screens but are the same gene [14].)…”
Section: Resultsmentioning
confidence: 99%
“…For example, SPT13 (GAL11) is a negative regulator of Tyl transcriptional activity but a positive regulator of some mating-specific genes such as MFal (14). (The SPT13 and GALII genes were identified by different mutational screens but are the same gene [14].) Although it is not known how SPT13 (GAL11) acts to modulate transcriptional activation, studies by Yu and Fassler reported in the accompanying article (37) show that SPT13 exerts its negative effects through the regulatory sequence in Tyl that binds to MCM1.…”
Section: Resultsmentioning
confidence: 99%